Assessing the reliability of microbial bioerosion features in burnt bones: a novel approach using feature-labelling in histotaphonomical analysis - Végh, Emese I.; Czermak, Andrea; Márquez-Grant, Nicholas; Schulting, Rick J. (Elsevier, 2021)
Objectives Recent histotaphonomic studies have focused on the presence of features thought to be caused either by bacteria (microscopic focal destruction/MFD and cyanobacterial tunnelling) or fungal (Wedl tunnelling types 1 and 2) attack on unburnt bone. Identifying these characteristics on burnt bones could indicate the state of decomposition before burning, with important repercussions for both archaeological and forensic contexts. Materials and Methods Fleshed pig (Sus scrofa, N = 25) tibiae were left exposed on a field, then collected at 14-, 34-, 91-, 180-, 365-day intervals before being burnt in an outdoor fire (≤750 °C). Fresh (fleshed) legs (N = 10) acted as unburnt and burnt controls. Thin sections were examined using transmitted light microscopy and backscattered scanning electron microscopy. Diagenetic traits were quantitatively and systematically assessed by a novel data labelling application developed for this study. Results Features meeting the published characteristics of microbial bioerosion (‘Wedl tunnelling’, ‘lamellate’ and ‘budded MFD’) were significantly correlated with time since deposition on the unburnt bones. Only budded MFD increased significantly over time in the burnt groups. However, the presence features meeting the published characteristics of Wedl 2 tunnelling were present on the fresh burnt bones, indicating that they are an artefact. Discussion The presence of many features seemingly indistinguishable from those caused by bioerosion on the freshly burnt control bones suggests that burning is not only able to conceal features thought to be the result of bioerosion but can produce them as well. Thus, such features are not a reliable indication of bioerosion. Budded MFD may be a viable indicator but more research is required.
Keywords: Microbial bioerosion; Burning; Bone; Cremation; Taphonomy